2001
DOI: 10.1046/j.0022-202x.2001.01546.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Density-Regulated Chemotactic Responsiveness of Keratinocytes In Vitro

Abstract: Keratinocytes represent the main constituents of the epidermis and have been found to play a regulatory role in a variety of inflammatory skin diseases. The functional activity of keratinocytes is highly heterogeneous, and depends on the cell localization in the epidermal architecture, and the maturation or differentiation state of the cells. Spontaneously proliferating HaCaT cells, showing several similarities to basal epidermal keratinocytes, were found to respond to external chemoattractants, including the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 64 publications
3
14
1
Order By: Relevance
“…We have previously reported that HaCaT keratinocytes produce constitutive RANTES in a cell-density-regulated manner. We have found that in the logarithmic growth phase of cultures the RANTES production graduately decreased [Szabo et al, 2001b]. In the present study we found that LP-MW irradiation of HaCaT keratinocytes did not significantly modulate constitutive RANTES production.…”
Section: Discussioncontrasting
confidence: 57%
“…We have previously reported that HaCaT keratinocytes produce constitutive RANTES in a cell-density-regulated manner. We have found that in the logarithmic growth phase of cultures the RANTES production graduately decreased [Szabo et al, 2001b]. In the present study we found that LP-MW irradiation of HaCaT keratinocytes did not significantly modulate constitutive RANTES production.…”
Section: Discussioncontrasting
confidence: 57%
“…In order to study this hypothesis, experiments were carried out using the human origin HaCaT keratinocytes, developing multilayers in dense in vitro cultures, thus providing a sufficiently large cell surface area for plasma coagulation within the beam [Szabo et al, 2001]. HaCaT cultures in small Petri dishes (35 Â 10 mm; equivalent dimensions with wells in a sixwell tissue culture plate used for blood exposures) were cooled to 4 8C and covered by cold human plasma before exposure with MMW.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, opioids have mitogenic properties in the regeneration of mucosa (Cho et al, 2003), promote reepithelialization and keratinocyte migration (Szabo et al, 2001;Bigliardi et al, 2002;Kü chler et al, 2010), and up-regulate cytokeratin and transforming growth factor-␤ receptors, both important components in wound healing (Tegeder and Geisslinger, 2004; for review, see Bigliardi et al, 2009). In ischemic wounds, locally applied opioids hastened wound closure increased granulation tissue and collagen formation, increased epidermal and dermal organization, and enhanced angiogenesis (Poonawala et al, 2005;Gross et al, 2009).…”
Section: Peripheral Pain Inhibitionmentioning
confidence: 99%